Pengaruh People dan Physical Evidence terhadap Kepuasan Pasien Rawat Inap pada RSUD Ahmad Ripin Muaro Jambi - Riko Mappadeceng; Fadil Iskandar; Delia Rustiela (Universitas Batanghari Jambi, 2022)
Hospitals have a very strategic role in the effort to accelerate the improvement of human health status. Health problems have become a basic need for the community, several empirical studies on people's satisfaction and physical evidence give inconsistent results where some studies show that people and physical evidence have no significant effect on satisfaction, but on the other hand there are also studies that show different things. Based on this explanation, the researcher is interested in submitting the research title